(untitled) (INNOVATIVE ECONOMY, 2026)
Kravchuk N.O. INTELLECTUAL CAPITAL IN THE HUMAN RESOURCE MANAGEMENT SYSTEM AS A STRATEGIC RESOURCE FOR ENTERPRISE DEVELOPMENT Purpose. The aim of the article is to provide a theoretical substantiation and develop applied principles for managing intellectual capital within the personnel management system as a strategic resource for enterprise development. Methodology of research. The study applies a set of general scientific and special research methods. The method of theoretical generalization is used to clarify the essence of intellectual capital and its components; the systems approach is applied to reveal the interrelationship between intellectual capital and personnel management functions; structural and logical analysis is used to develop a model for integrating intellectual capital management into the enterprise HR strategy; the tabular method is applied to systematize the components of intellectual capital, HR mechanisms for its formation and assessment indicators; the analytical method is used to interpret statistical data on Ukraine’s research and development potential and the country’s positions in the Global Innovation Index; the case study method is applied to summarize practical examples of intellectual capital management in the activities of modern enterprises. Findings. The article clarifies the content of enterprise intellectual capital as a combination of human, structural and customer capital that ensures value added creation, innovation, adaptability and long-term competitiveness of an enterprise. It is proved that the personnel management system is a key mechanism for the formation, development, preservation and commercialization of enterprise intellectual capital. The study analyses selected indicators of the state of Ukraine’s societal intellectual potential, in particular the dynamics of the number of employees involved in research and development, as well as Ukraine’s positions in the Global Innovation Index. It is established that Ukraine retains significant potential in the fields of knowledge, technological outputs, human capital and research, particularly under martial law. The article examines the experience of rational intellectual capital management in modern companies, in particular through the use of corporate training tools, processes of involving personnel in research and development activities, patent activity, digital services and employer brand development. The proposed model for integrating intellectual capital management into the human resources management system comprises the following key stages: diagnosis, strategic planning, human capital development, structural capital formation, consumer capital development, and performance evaluation. The practical value of this model lies in improving the effectiveness of managing the elements of an enterprise’s intellectual capital and ensuring their alignment with the business entity’s overall development strategy. Originality. Approaches to the interconnection between intellectual capital management processes and the functions of an organisation’s human resource management – in particular, recruitment, induction, staff training, as well as talent development, motivation and knowledge management – have been further developed. A model for integrating intellectual capital management into an organisation’s human resource management strategy is proposed, which enables the transformation of employees’ individual knowledge into organisational competencies and strategic competitive advantages for the organisation. Practical value. The proposed system of indicators for assessing intellectual capital can be used by HR departments and enterprise managers to diagnose the state of human, structural and customer capital, as well as to make strategic managerial decisions regarding enterprise personnel development. Key words: intellectual capital, human capital, structural capital, customer capital, personnel management, knowledge management, talent management, HR strategy, innovative development, strategic resource of enterprise.